Ethics committee laws, penalty comparison across globe: a mandatory thought before accreditation process in India - Raibagkar, Stuti; Majmudar, Falguni D.; Rana, Devang A. (International Journal of Research in Medical Sciences, 2017)
To have a better quality of life and to fight with the diseases evolved the concept of clinical trials. A test of any new or existing drug on human being through different phases to check the efficacy and safety of the molecule is clinical trial. To cope up with the defects in drug system, India introduced Drugs and Cosmetics Act, 1940 and Drugs and Cosmetics Rules in 1945. Objective: To compare and contrast the different GCP guidelines and law suits, penalties, worldwide. We reviewed different internet databases and resources to find out the various penalties. The death occurring during clinical trials shook the pillars of credibility of clinical trials and led the government to make some regulatory provisions. The outcome is that now the ethics committee has to be accredited by a competent authority. This step led many problems for upcoming as well as the existing ethics committee and trial sites. The objective of the review article is to know the roles and responsibilities of different players of clinical trials i.e. the investigator, the sponsor and the ethics committee and to know the laws governing their responsibilities and the penalties affiliated to it. Since now the clinical trials in India are becoming more and more stricter there is a dire need to make aware the ethics committee members, sponsor and the investigator of their rights and duties towards one another and towards the patient/subject, so the tragedies in the clinical trials can be minimized.